2018
DOI: 10.1093/neuros/nyy010
|View full text |Cite
|
Sign up to set email alerts
|

Prerupture Intracranial Aneurysm Morphology in Predicting Risk of Rupture: A Matched Case-Control Study

Abstract: BACKGROUND Maximal size and other morphological parameters of intracranial aneurysms (IAs) are used when deciding if an IA should be treated prophylactically. These parameters are derived from postrupture morphology. As time and rupture may alter the aneurysm geometry, possible morphological predictors of a rupture should be established in prerupture aneurysms. OBJECTIVE To identify morphological parameters of unruptured IAs associated with later ruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…A recent Norwegian nationwide case-control study simi- larly found traditional aneurysm morphology parameters could not predict rupture risk. 37 Ruptured and unruptured aneurysms may therefore represent different populations and/or have different pathogeneses, 15 with SAH resulting from aneurysms that rupture a short time after formation, leaving little time for detection and treatment while unruptured. 20,46 This may explain the discrepancy between the observation that most aneurysms presenting with rupture are small (< 7 mm), whereas similarly sized unruptured aneurysms appear to have a low risk of rupture.…”
Section: Impact On Sahmentioning
confidence: 99%
“…A recent Norwegian nationwide case-control study simi- larly found traditional aneurysm morphology parameters could not predict rupture risk. 37 Ruptured and unruptured aneurysms may therefore represent different populations and/or have different pathogeneses, 15 with SAH resulting from aneurysms that rupture a short time after formation, leaving little time for detection and treatment while unruptured. 20,46 This may explain the discrepancy between the observation that most aneurysms presenting with rupture are small (< 7 mm), whereas similarly sized unruptured aneurysms appear to have a low risk of rupture.…”
Section: Impact On Sahmentioning
confidence: 99%
“…Relying too much on aneurysm size may thus cause overtreatment of large but benign aneurysms, and undertreatment of small but dangerous ones. In addition to patient factors, treatment decisions can be supported by aneurysm factors such as morphology and hemodynamics [2,[16][17][18], and magnetic resonance vessel wall imaging [19,20].…”
Section: Treatment Volumementioning
confidence: 99%
“…This life-threatening clinical condition has an acute mortality rate of approximately 50% [5,6]. Despite considerable advances in therapy for IAs, SAH remains a highly lethal condition which is associated with a high socioeconomic burden [7][8][9]. Thus, an ability to identify IAs which have a high risk of rupture and provide timely preventive treatment may be key to the successful management of IAs.…”
Section: Introductionmentioning
confidence: 99%
“…To predict IA rupture, researchers have studied aneurysmal hemodynamics [10,11], aneurysmal morphology and location [8], genetics [12], and other factors (e.g., cigarette smoking, hypertension, and positive family history for SAH) [13]. Only inflow angle was identified as a significant predictor of rupture according to morphological parameters [8]. However, aneurysm wall inflammation has also been shown to play a pivotal role in aneurysm growth and rupture [2,3,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation